2010
DOI: 10.1038/ejcn.2010.17
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a database on acrylamide for use in epidemiological studies

Abstract: Background/Objectives: Acrylamide, a probable human carcinogen, was detected in various heat-treated foods such as French fries and potato crisps. Recently, positive associations have been found between dietary acrylamide intakes, as estimated with a food frequency questionnaire using an acrylamide database, and cancer risk in some epidemiological studies. As acrylamide levels vary considerably within the same type of foods, a validation study was performed to investigate whether use of an acrylamide food data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…From the national dietary survey in Japan in 2012, acrylamide intake was estimated by Monte Carlo simulation to be 0.166 μg/kg bodyweight per day . This level is less than half of that reported in Western populations, namely 0.45 μg/kg bodyweight per day in the Dutch and 0.41 μg/kg bodyweight per day in Norwegians . These levels are lower than in animal studies; however, when the benchmark dose lower confidence limit (BMDL 10 ) is 0.31 mg/kg bodyweight per day for mammary tumors in rats, the MOE is <10 000 .…”
Section: Introductionmentioning
confidence: 64%
“…From the national dietary survey in Japan in 2012, acrylamide intake was estimated by Monte Carlo simulation to be 0.166 μg/kg bodyweight per day . This level is less than half of that reported in Western populations, namely 0.45 μg/kg bodyweight per day in the Dutch and 0.41 μg/kg bodyweight per day in Norwegians . These levels are lower than in animal studies; however, when the benchmark dose lower confidence limit (BMDL 10 ) is 0.31 mg/kg bodyweight per day for mammary tumors in rats, the MOE is <10 000 .…”
Section: Introductionmentioning
confidence: 64%
“…Moreover, a recent study has shown that it is feasible to make a sound rank ordering of the acrylamide intake via a 24-hour meal using the mean acrylamide levels used in the NLCS study for individual foods. [27]. Secondly, the acrylamide values in our food database were derived from foods that were sampled in 2002 and 2005.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the acrylamide level for each food, the mean values of the acrylamide measurements per food were used, or, in case the concentrations were lower than the quantitation limit, a value one-half the quantitation limit. This database was recently validated in a study comparing estimated acrylamide content (using acrylamide data from the database) and measured acrylamide content of duplicate 24-hour diets [27]. This rendered a correlation coefficient of 0.82, which indicates that it is feasible to make a sound rank ordering of the acrylamide intake via a 24-hour meal using the mean acrylamide levels for individual foods in the database.…”
Section: Methodsmentioning
confidence: 99%
“…The EU database was set up to permit monitoring of acrylamide levels in food products throughout the whole EU, which includes the UK. A recent validation study compared estimated acrylamide intake based on average acrylamide levels of food items, such as those available in the EU database, compared with chemically analysed content (Konings et al , 2010). The correlation between chemically determined acrylamide content and estimated acrylamide content was very high, indicating that using single acrylamide values for individual foods based on average values of several available samples, such as that reported in the EU database, results in a good rank ordering of most subjects, despite the large variation of acrylamide concentrations within single foods.…”
Section: Methodsmentioning
confidence: 99%